Will Traynor’s Suicidal Decision as Depicted in Novel Me Before You by Jojo Moyes - Lody Kristiyawan Mustafa; Jumino Jumino (Department of Linguistics, Faculty of Humanities, Diponegoro University, 2021)
In this project, the writer analyzes Will Traynor’s suicide decision which is reflected in novel “Me Before You” by Jojo Moyes. This paper used close reading method and psychological approach to analyze the story. The project aims to discuss Will Traynor suicide decision and how it is affecting to the other characters in the story. Through the analysis in this paper, the writer found several things that influenced Will Traynor suicide decision which was his characteristic, his internal and external conflict, and his psychological aspect. The writer also found that the other characters are really affected by Will’s decision.Keywords: Jojo Moyes; suicide; intrinsic; close-reading; characteristic